PELATIHAN PENGOLAHAN JAMUR TIRAM MENJADI NUGGET DI KELURAHAN TERUMBU KECAMATAN KASEMEN KOTA SERANG - Mahpudoh Mahpudoh; Kaustar Yuwono; Rizki Yogaswara; Risya Aulia Putri (Indonesian Collaboration Journal of Community Services, 2021)
The purpose of the Student Work Community Service Program is to improve the skills of the community of Kasemen District Of Serang District. The partner of this activity is the Sampang village community, which is the centre of oyster mushroom production in the reef village. The problem faced is the lack of innovation in the processing of oyster mushrooms that attract consumer interest and have selling value. During this time, the oyster mushrooms are only marketed in the original form without any other form of processing. This method of devotion is through (1) surveys through observation, interview, and analysis of problems and potential villages, (2) training in making and packaging oyster mushroom nuggets. The result of this program is the increasing knowledge and skills of the community in making innovations from the processing of oyster mushrooms. This program is expected to improve the economy of the community, especially the residents of Reef villages